2015
DOI: 10.1007/s13277-015-3637-2
|View full text |Cite|
|
Sign up to set email alerts
|

Impairment of growth of gastric carcinoma by miR-133-mediated Her-2 inhibition

Abstract: Gastric carcinoma (GC) is a leading cause of cancer-related death in China. Dysregulation of microRNAs (miRNAs) has been shown to contribute to the development of GC, whereas the role of miR-133 in GC is unknown. Here, we analyzed the levels of miR-133 in GC tissues by reverse and quantitative transcription polymerase chain reaction (RT-qPCR). We overexpressed or inhibited miR-133 in GC cells. Cell growth was analyzed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and cell apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It has been reported that miR-132, miR-15a, and miR-16 can suppress the migration and invasion of pituitary tumor cells during its metastasis (Bottoni et al, 2007;Palumbo et al, 2013). miR-133 is relatively less studied but, recently, a potential role for miR-133 in gastric cancer and its molecular mechanisms have been reported (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that miR-132, miR-15a, and miR-16 can suppress the migration and invasion of pituitary tumor cells during its metastasis (Bottoni et al, 2007;Palumbo et al, 2013). miR-133 is relatively less studied but, recently, a potential role for miR-133 in gastric cancer and its molecular mechanisms have been reported (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One of these miRs, miR-133, has been shown to play a role in tumor suppression in a variety of cancers, including inhibiting breast cancer cell migration and invasion, gastric cancer cell growth and migration, and liver fibrosis (Esquela- Kerscher and Slack, 2006;Cheng et al, 2012;Liu et al, 2014;Mei et al, 2014;Wang et al, 2014;Yongchun et al, 2014;Xie et al, 2015;Zhang et al, 2015). Recent studies have shown that miRs may be a new regulatory mechanism involved in the onset of pituitary adenoma, providing a new method for the diagnosis and treatment of pituitary adenoma (Trivellin et al, 2012;Gadelha et al, 2013;Di Ieva et al, 2014;Leone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This result was confirmed in GC cell lines and primary GC tissues by both microarray and qPCR methods. The level of miR-133 in GC and corresponding non-tumour tissues was detected in three different groups of GC patients independently (59)(60)(61). Results further revealed that miR-133 reduction is more likely to perform worse in tumour size, invasion depth and peripheral organ metastasis.…”
Section: Mirs In Gcmentioning
confidence: 86%
“…Dysfunction of miR-133 was an independent prognosis factor for overall survival (60,61). Moreover, by luciferase assay, miR-133 was proved to target 3'UTR of EGFR and HER-2, which may cut cell growth signals off, and inhibits cell growth ultimately promoting apoptosis (59). These related research results of miR-133 in GC as a whole have elucidated a novel mechanism for oncogene inhibition by miRNA-mediated pathways and offer new avenues for GC treatment.…”
Section: Mirs In Gcmentioning
confidence: 90%
“…the carcinogenesis and development of gastric cancer. But few studies have revealed the relationship between miRNAs and EGFR in gastric cancer (16,17).…”
Section: Mir-455 Inhibits Cell Proliferation and Migration Via Negatimentioning
confidence: 99%